Planning budgets and their impact on management function and performance measurement in banks - Al Momani, Tayseer Ali Khalaf (Journal of Economic, Administrative and Legal Sciences, 2017)
This research is conducted to identify the measurement of planning budgets and their impact on management function and performance measurement in banks, as well as their impact on various management functions, including long-term planning, with performance measurement. The study found that there is an effect on the use of planning budgets in Jordanian commercial banks by increasing the administrative efficiency and achieving the competitiveness of the bank. The planning budgets contribute to the interpretation of the budget of the bank. Strategic plans, optimal utilization of resources, increased profitability and long-term planning. Budgets reflected the future plans of the banks' general budgets and contributed to timely management decisions. There is also an impact on the process of performance measurement as the budget is a general tool for improving the efficiency of management. It also reflects the expectations of senior management and management control. The bank, which found a contribution in interpreting deviations, has a role in supervising the performance of employees.
Keywords: Budget; performance measurement; evaluation; efficiency; strategy